Krieg dem Kriege; Guerre à la guerre - Patocchi, Aldo (1907-1986); SABZ / GEO seit/depuis 1912, Pf. 54, 3000 Bern 23; SABZ / GEO seit/depuis 1912, Pf. 54, 3000 Bern 23 (1934)
Holzschnitt, Plakat und Postkarte für die Sozialistische Jugend der Schweiz;